The Effect of Nanowire Gap for Silicon Nanowire Transistor to the Current-Voltage (I-Vds) - Abdullah, Ahmad Makarimi; Yaacob, Khatijah Aisha; Alias, Nurain Najihah; Mohd Azmi, Mohd Azraie; Abd Manaf, Asrulnizam (Journal of Science and Technology, 2023)
One-dimensional structures are attracting a lot of attention for optimizing applications as one of the most sensitive devices. Among the fabricated devices, silicon nanowires (SiNW) and silicon nanowire transistors (SiNWT) are of particular importance for promising applications fabricated using bottom-up or top-down approaches to nanoscale devices. In this paper, the sensitivity of the current-voltage characteristic to the nanowire gap of a silicon nanowire transistor (SiNWT) was analyzed. SiNWTs with different nanowire gaps were fabricated using scanning probe microscopy by local anodic oxidation (LOA). Varies gaps can be occurring during the fabrication processes and its can be controlled by RASTER programming in LAO. These gaps can give different results of the sensitivity to the volt-ampere response. However, these gaps can be neglected depending on the subject of the studies and important to the other study, especially in nano particle sensors. In this experiment, the nanowires gaps were developed in the range of 100.5-435.6 nm and had been plotted the measurement data with the volt-ampere response. The data was analyzed using a semiconductor analyzer connected to a HP 4156C SPA series software analysis model from Desert Cryogenics. From the results had been measured the Current-Voltage (IV) increases proportionally with the nanowire gap distance in the SINWT device and these results will give significant effects to the application in nanoparticle sensors.